Diesel exhaust inhalation exposure induces pulmonary arterial hypertension in mice. (June 2018) - Liu, Jing; Ye, Xiaoqing; Ji, Dapeng; Zhou, Xiaofei; Qiu, Cong; Liu, Weiping; Yu, Luyang
Abstract: Diesel exhaust (DE) is one of the main sources of urban air pollution. An increasing number of evidence showed the association of air pollution with cardiovascular diseases. Pulmonary arterial hypertension (PAH) is one of the most disastrous vascular diseases, which results in right ventricular failure and death. However, the relationship of DE inhalation exposure with PAH is still unknown. In this study, male adult mice were exposed by inhalation to filtered ambient air (negative control), 10% O2 hypoxia (PAH-phenotype positive control), 350 μg/m 3 particulate matter whole DE, or the combination of DE and hypoxic condition. DE inhalation induced PAH-phenotype accompanied with increased right ventricular systolic pressure (RVSP), right ventricle hypertrophy and pulmonary arterial thickening in a mouse model. DE exposure induced the proliferation of vascular smooth muscle cells (VSMCs) and apoptosis of endothelial cells in pulmonary artery. DE inhalation exposure induced an accumulation of CD45 + lymphocytes and CD68 + macrophages surrounding and infiltrating pulmonary arteriole. The levels of pro-inflammatory cytokines tumor necrosis factor (TNF-α), interleukin-6 (IL-6) and IL-13 produced by T helper 17 (Th17) and Th2 cells were markedly elevated in lung tissues of mice after DE inhalation exposure. Our findings suggest DE exposure induces PAH by activating Th17-skewed and Th2-droved responses, stimulating VSMCs proliferation and inducing endothelial cell apoptosis by the production of multifunctional pro-inflammatory cytokines, especially IL-6 and TNF-α. Considering the adverse impact of air pollution on health care, it is imperative to understand air pollution-induced susceptibility of progressive cardiopulmonary disease, such as PAH, and also elucidate critical mechanistic pathways which mediate pulmonary artery vascular remodeling and may serve as targets for preventive measures. Graphical abstract: Image 1 Highlights: DE inhalation exposure induced PAH-phenotype in mice. DE exposure induced pulmonary artery vascular remodeling. DE exposure induced pulmonary inflammation by production of cytokines.